CLAIMS FOR A STATEMENT AND DEBATEMENT OF ACCOUNT: PRINCIPLES AND PROCESS - RC Williams (Obiter, 2023)
Where a party is owed a sum of money by another party but is unable to quantify the claim because the relevant information and documentation is in the hands of the debtor, the first-mentioned party will in certain circumstances be entitled to demand, and if necessary institute legal proceedings to compel, the alleged debtor to furnish a statement of account, followed by engagement in a debatement of the account. However, creditors have no general right to demand that a debtor either provide a statement of account or engage in a debatement. This article examines the circumstances in which a creditor has such a right and the powers of the court in this regard.